Relapse and recovery in addictions - Tims, Frank M.; Leukefeld, Carl G.; Platt, Jerome J. (Yale University Press, 2001)
In this book leading experts in the field of addictions report on key aspects of addictive disorders. They focus particularly on relapse, the long-term course of addiction to drugs or alcohol, and interventions to prevent relapse and promote recovery. A critical and highly complex public health problem, addiction is seen today as having biological, psychological, social, and cultural aspects. This important volume brings together the major perspectives on addiction, treatment, and recovery along with the current findings of clinical and scientific research. For those working with addicted patients and those making policy decisions that affect treatment and its availability, this book is an essential reference.